Conditions for the Use of Analogia Legis - Kaźmierczyk, Aneta (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The article examines analogia legis, the application of a legal rule to the facts of a similar but not by law regulated case. It starts with a discussion of the concept of analogia legis, followed by a look at conditions that enable the use of this type of reasoning and an examination of legal loopholes in order to determine the similarity between the facts not covered by normalisation and an actual state regulated by the law. The circumstances that would preclude the application of analogia legis are identified. Finally, other ways of drawing inferences from the rules of law beyond analogia legis are outlined.